Konstruksi Sosial Pendidikan: Menjembatani Teori Sadd al-Dzari’ah dan Praktik Pencegahan Perkawinan Dini pada Masyarakat Muslim di Lombok Tengah - Sahdan Sahdan; Abdul Haris Rasyidi (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
Early marriage remains a persistent social phenomenon in Indonesia, including in Central Lombok, fueled by cultural traditions, economic pressures, limited access to education, and religious interpretations within the community. This article examines the application of sadd al-dzari’ah an Islamic legal concept emphasizing the preventive closure of paths leading to harm as a theoretical and practical framework for preventing early marriage in the Muslim community in Central Lombok. Using a qualitative, normative-sociological methodology that combines literature review, legal document analysis, and a review of previous research, this article demonstrates that sadd al-dzari’ah is highly relevant in addressing the negative impacts of early marriage, including school dropout, psychological unpreparedness, marital conflict, high divorce rates, and health risks for mothers and children. This framework aligns with the broader objectives of maqashid al-syariah in protecting life, offspring, intellect, property, and religion. From the perspective of the social construction of education, knowledge about the harms of early marriage is not natural but socially constructed through educational processes, religious sermons, and institutional interactions. Practical implementation can be realized through premarital education, strengthened regulations, awareness campaigns led by religious leaders, and stricter oversight of marriage dispensation practices. Research findings indicate that sadd al-dzari’ah transcends its function as an abstract jurisprudential concept and operates as an actionable instrument to promote family well-being and strengthen the social construction of education in Muslim communities.